Inhibition of Bacterial Growth by Lawsonia inermis (henna) Leaf Extracts In Vitro - M. A. Merdaw (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
Leaf samples of Lawsonia inermis were collected from Basrah city, South of Iraq to examine their antimicrobial activity . The effects of water and chloroform crude extracts of the leaves in different concentrations were obtained and bioassayed in vitro for its bioactivity to inhibit the growth of six types of bacteria . The extract of water was clearly superior for all bacteria especially the bacteria Staphlylococcus aureus (inhibition zone was 21mm in concentration 70mg/ml) from gram positive bacteria, and Klebsiella pneumoniae (inhibition zone was 20mm in the same concentration)  , and the growth of all bacteria was inhibited to varying degrees by increasing the concentration of the henna leaves and are commonly known to possess antimicrobial activity . These results confirm the antibacterial activity of henna leaves and support the traditional use of the plant in therapy of bacterial infections .